Post-Kidney Transplantation Results After Circulatory or Brain Death Without Pre-Mortem Heparin Administration - Roman, Jan; Jalůvka, František; Ostruszka, Petr; Jelínek, Petr; Hrubovčák, Ján; Havránek, Pavel; Vrtková, Adéla; Lys, Zdeněk; Dědochová, Jarmila; Procházka, Václav (Medical science monitor, 2022)
BACKGROUND Kidney donation after circulatory death (DCD) follows confirmation of death using cardiorespiratory criteria, while donation after brain death (DBD) uses neurological criteria. DBD and DCD donors are the main sources of grafts for transplantation. This retrospective cohort study from a single center in the Czech Republic aimed to compare 5-year post-transplantation outcomes after DCD and DBD transplantation without pre-mortem heparin administration. MATERIAL AND METHODS A total of 227 recipients with matched donors enrolled in the transplantation program at our institution between 2015 and 2019 were analyzed. Following the application of the inclusion criteria, 99 recipients and 94 matched donors were finally included in the study. RESULTS The duration of cold ischemia (median 961 vs 1100 min, P=0.028) and the perfusion with the preservation solution (median 11 vs 22 min, P<0.001) was statistically significantly shorter in DBD than in DCD grafts. The 1-year survival rates were 97.5% (95% CI 94.1-100.0%) and 90.0% (95% CI: 77.8-100.0%) for DBD and DCD recipients, respectively. The 3-year survival rates were 91.9 (95% CI: 86.0-98.4) and 90.0 (95% CI: 77.8-100.0) for the DBD and DCD groups, respectively. The overall difference in survival between the 2 groups of patients was not statistically significant (P=0.750) nor was disease-free survival (P=0.370). CONCLUSIONS This retrospective study from a single center showed similar 5-year results after kidney transplantation for DCD and DBD donors without pre-mortem heparin administration, including the time to graft failure and patient survival.
Keywords: heparin; přežívání štěpu; transplantace ledvin; lidé; Graft Survival; Kidney Transplantation; retrospektivní studie; Humans; mozková smrt; Retrospective Studies; Heparin; Brain Death